Visions of Scotland [videorecording (DVD)] - Toperoff, Sam (Acorn Media, 2007)
"See bonny Scotland as you never could, even on the most lavish tour. Thanks to a helicopter-mounted camera, you soar effortlessly over Scotland's historic cities, tranquil villages, rugged highlands, and steel-blue lakes."--Container.